Quantitative assessment of neural outgrowth using spatial light interference microscopy - Lee, Young Jae (J Biomed Opt, 2017)
Optimal growth as well as branching of axons and dendrites is critical for the nervous system function. Neuritic length, arborization, and growth rate determine the innervation properties of neurons and define each cell’s computational capability. Thus, to investigate the nervous system function, we need to develop methods and instrumentation techniques capable of quantifying various aspects of neural network formation: neuron process extension, retraction, stability, and branching. During the last three decades, fluorescence microscopy has yielded enormous advances in our understanding of neurobiology. While fluorescent markers provide valuable specificity to imaging, photobleaching, and photoxicity often limit the duration of the investigation. Here, we used spatial light interference microscopy (SLIM) to measure quantitatively neurite outgrowth as a function of cell confluence. Because it is label-free and nondestructive, SLIM allows for long-term investigation over many hours. We found that neurons exhibit a higher growth rate of neurite length in low-confluence versus medium- and high-confluence conditions. We believe this methodology will aid investigators in performing unbiased, nondestructive analysis of morphometric neuronal parameters.